Seleção de clones de batata-doce para diferentes aptidões agronômicas - Silva, Jeferson Carlos de Oliveira (2019)
The genetic improvement of sweet potato (Ipomoea potatoes (L.) Lam.) is based on the selection and recombination of adapted and productive genotypes in a given region. By adapting technologies and basic cultivation methods to the crop, higher root and branch yields are achieved according to its different aptitudes. The objective of this study was to identify the agronomic suitability of sweet potato genotypes from botanical seeds of traditional Brazilian progenies, and to select them for human consumption, ethanol production and animal feeding through aptitude indices. For the experimental design, incomplete blocks with row and column control combined with kinship restriction in the drawing were used. A total of 1604 half-sibling genotypes were evaluated. The genotypes come from the recombination of 55 progenies from the germplasm collection of the Universidade Federal de Lavras (UFLA). Two accessions (UFVJM 61 and UFVJM 58) belonging to the germplasm bank of the Universidade Federal dos Vales do Jequitinhonha e Mucuri (UFVJM) were also included in the evaluation as control treatments. The aptitude indices corresponded to the averages of the values of the 13 evaluated characters, in which weights were attributed to each characteristic according to the evaluated aptitude. The data was transformed and standardized for the three aptitudes of interest. The most promising genotypes were selected by the mixed model through BLUP in relation to the evaluated characteristics and the aptitude of interest, using the Zi index and taking into account the kinship between half siblings with 2.5% selection pressure. Nine selectable progenies have been identified for breeding programs: for ethanol production - progenies 1; 14; 18; 19; 55; 68 and 72, for animal feeding - progenies 1; 14; 18; 19; 55; 61; 68; 72 and the control UFVJM 58, and for human consumption - progenies 1; 14; 18; 55; 68; 72 and the control UFVJM 58. The progenies that showed multiple aptitudes were: 1, 14 18, 55, 68 and 72, UFVJM 58 progeny for double aptitude (animal and human consumption), progeny 19 with double aptitude (animal and ethanol production) and progeny 61 for unique aptitude (to animal feed). It was identified that 60 genotypes met one or more proposed aptitudes. For example, 37 genotypes plus two controls can be apt for ethanol production, 36 genotypes plus two controls are apt for animal feeding and 38 genotypes plus one control (UFVJM 58) can be apt for human consumption. The genotypes 556; 765; 1221; 1231; 1319 and control UFVJM 61 are considered apt for ethanol production and animal feeding. The genotypes 220; 301; 455; 736 and 1311 are considered apt for human consumption and ethanol production. The genotypes 49; 181; 314; 660; 663; 716; 1000; 1164; 1238; 1258 and 1538 are considered apt for animal feeding and human consumption. The genotypes 161; 221; 225; 238; 450; 540; 655; 759; 791; 799; 1008; 1234; 1252; 1299; 1562 and control UFVJM 58 are considered apt for ethanol production, animal feeding and human consumption. The genotypes 11; 107; 354; 546; 574; 695; 884; 987; 1005; 1011; 1235 and 1565 present unique suitability for ethanol production. The genotypes 290; 829; 1210; 1288 and 1436 present unique suitability for animal feeding. The genotypes 106; 144; 404; 622; 648; 992 and 1554 show unique suitability for human consumption. Thus, the results obtained in this study provide efficient information for breeding programs. Faced with the generation of this new variability, it is possible to study cultivars, subsidizing national food independence, which represents an important social contribution.